Accounting and Statistics in China during the Ming Dynasty - M. A. Amurskaya (Учёт. Анализ. Аудит)
Chinese experience attracts more and more researchers from all over the world, as the country has convincingly demonstrated economic success in recent decades. This study was carried out using methods of observation, sampling, grouping, systematization, comparison, generalization. The theoretical and practical materials in Chinese, Russian, and English were explored using a historical approach. the author highlighted the main milestones in the development of the national economy during the Ming dynasty (early, middle, and late periods) and noted their features. The principal normative documents regulating the statistics of the national economy and accounting have been brought in, including the “Laws of the Great Ming Dynasty.” The basics of state management of statistical and accounting work, based on the activities of six ministries, are considered. The practical significance of the work lies in highlighting the methods of analysis of demographic statistics, including “Hute” checkpoint system, accounting methods through the Yellow and White Book, “Baojia” accounting system, “Qianliang Zhangbu” accounting and reporting system using a “four-column ledger”, as well as the basics of property inventory. The article presents the research, ideas, and practical recommendations of such Chinese outstanding thinkers and scientists as Qiu Jun, Zhang Jiuzheng, Xu Guangqi, Lu Xiangsheng.